Vanessa Burkoski, 2012 Winner, Margret Comack Award for Nursing Leadership (Nursing Leadership, 2013)
Vanessa Burkoski, RN, BScN, NP-PHC, MScN, DHA, was the recipient of the Margret Comack Award for Nursing Leadership, which was presented at the 2012 HealthAchieve conference in Toronto.
Keywords: Vanessa Burkoski, Margret Comack, award